2006
DOI: 10.1080/03670240600985464
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Use of Animal Source Foods for Young Children in Ghana: A Participatory Rapid Appraisal Approach

Abstract: Micronutrient deficiencies limit child health and development. Although animal source foods (ASF) provide highly bioavailable micronutrients, Ghanaian preschoolers consume little. Participatory rapid appraisal methods identified constraints to the availability, accessibility, and utilization of ASF. Stakeholders working with or living in six communities in three agro-ecological zones reported constraints including low income, lack of access to technology and markets, inequitable household food allocation, inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 13 publications
8
33
1
Order By: Relevance
“…Because eggs are relatively higher in cost than staple foods like rice, maize, and other grains, they are often reserved for special occasions or provided to adult male household members . If purchased, eggs may not be fed directly to the child but instead may be mixed into a family pot and consumed by all household members, limiting the amount that a young child may actually consume . While some programs might consider subsidizing the cost of eggs for young children, this may be insufficient to overcome perceived economic barriers.…”
Section: Cultural Issues and Eggsmentioning
confidence: 99%
“…Because eggs are relatively higher in cost than staple foods like rice, maize, and other grains, they are often reserved for special occasions or provided to adult male household members . If purchased, eggs may not be fed directly to the child but instead may be mixed into a family pot and consumed by all household members, limiting the amount that a young child may actually consume . While some programs might consider subsidizing the cost of eggs for young children, this may be insufficient to overcome perceived economic barriers.…”
Section: Cultural Issues and Eggsmentioning
confidence: 99%
“…In times of food crises with households facing resource constraints, children may be given the lowest priority in terms of food allocation (Hampshire et al, 2009). One reason could be parental ignorance as to the importance of certain foods for children as was found in a study of the provision of animal source foods to children in Ghana (Colecraft et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In Ghana, the Demographic and Health Survey of 2008 showed that an estimated 70% of pregnant women and over 80% of children between 6 and 12 months of age were anaemic, and this is believed to be mainly due to inadequate iron intake. It is likely that the intakes of other key nutrients such as essential fatty acids (EFAs), zinc and vitamin A in these vulnerable groups are also low, given the low intakes of animal source foods especially among children (Colecraft et al . 2006 ).…”
Section: Introductionmentioning
confidence: 99%